Komunikasi Dalam Kepemimpinan Organisasi - Mu’alimin Mu’alimin; Larasati Afina Salsabilla; Sahawtul Jannah; Mohammad Zen Amrullah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Effective communication has a very important role in the success and performance of leaders in an organization. Focus on the strategies used to improve communication. Communication in an organization covers various aspects, including internal communication between leaders, team members, and departments. Thus, a deep understanding of the role of communication in organizational leadership becomes a real effort to improve communication and make a significant contribution to achieving organizational goals and improving overall performance. This research aims to explain communication in organizational leadership. This literature review was obtained from scientific research articles from 2018-2023 using Google Scholar in Publish or Perish (PoP) with the keywords "Communication in Organizations" and "Communication in Organizational Leadership" and after the identification process, 15 articles were obtained that were in accordance with purpose of the literature review based on the results of the literature review analysis, it can be concluded that communication in organizational leadership confirms that effective communication is the main key to the success of an organization. Good communication enables the formation of mutual understanding and the unification of experiences among organizational members, thereby smoothing the course of organizational activities.